Pengaruh Kegiatan English Fun Club dan Motivasi Belajar Terhadap Hasil Pembelajaran Mata Kuliah Bahasa Inggris Mahasiswa STIE AAS Surakarta - Dewi Muliasari (Institut Agama Islam Negeri Purwokerto, 2020)
This study aims to determine the effect of the English Fun Club and learning motivation on learning outcomes in English 2 STIE AAS Surakarta students. The theoretical benefit of this research is that it can add information and reference materials in the field of education, especially English courses so that the teaching can be optimal and can be used to add references for those who will carry out similar research. While the practical benefits of the results of this study can provide an overview of the influence of the English Fun Club extracurricular activities on the results of studies in the English language courses of STIE AAS Surakarta students and are expected to provide input for higher education in an effort to improve learning outcomes through providing motivation and deepening the material in the course. English in order to achieve maximum results. This research is a research using a quantitative approach. The population of this study was the students of STIE AAS semester IV Surakarta who took part in the English Fun Club, totaling 67 people in the even semester of the 2019/2020 academic year and all of them were taken as research subjects, so this research is also a population study or census. Data collection techniques using documentation and questionnaires. Test the validity of the instrument using Product Moment and reliability testing using Cronbach Alpha. The data analysis method used multiple linear regression analysis. The results of this study indicate that the English Fun Club and learning motivation significantly influence learning outcomes.